2002
DOI: 10.1159/000057764
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dye Diffusion and Upregulation of Connexin37 in Mouse Aortic Endothelium Deficient in Connexin40

Abstract: Connexin40 (Cx40), connexin37 (Cx37) and connexin43 (Cx43) are subunit proteins of gap junction channels in the vascular wall which are presumably involved in the propagation of vasomotor signals. In this study we have investigated in Cx40-deficient versus wild-type aortic endothelium to which extent loss of Cx40 impairs intercellular communication. We show in Cx40-deficient mice that expression of both Cx37 and Cx43 protein was increased approximately 3- and 2-fold over the level in wild-type endothelium, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 25 publications
6
55
2
Order By: Relevance
“…On the other hand, alterations within the vascular system have been shown previously in these mice (7,18). Moreover, irregular vasomotion patterns were observed (Fig.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, alterations within the vascular system have been shown previously in these mice (7,18). Moreover, irregular vasomotion patterns were observed (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, the hypertension is unlikely to be due to an activation of the renin-angiotensin system or to an activation of the sympathetic nervous system. The data show that the specific functions of Cx40 cannot be fully compensated by another member of the connexin family expressed in vascular cells despite endothelial upregulation and redistribution of Cx37 in Cx40-deficient mice (18). We propose that Cx40-dependent cell coupling has an important role in the control of peripheral vascular resistance and that defects in cell coupling within the vascular tree should be regarded as a possible cause of hypertension in humans.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with these findings, we did not detect expression of Cx43 protein in endothelium of wild-type mouse aorta, nor did we see compensatory expression of Cx43 in aortas from connexin knockout mice. Krüger et al also did not detect Cx43 in adult mouse aortic endothelium (Krüger et al, 2002). The absence of Cx43 from mouse arterial endothelium differs substantially from results obtained from rat and bovine studies (Yeh et al, 1997;Gabriels and Paul, 1998;Yeh et al, 1998;van Kempen and Jongsma, 1999).…”
Section: Discussionmentioning
confidence: 76%
“…endothelial coupling has not been fully investigated. While this work was in progress, Krüger et al investigated the effects of a deficiency of Cx40 and concluded that intercellular transfer of injected dyes was altered in Cx40-deficient aortic endothelium and that expression of endothelial Cx37 was upregulated (Krüger et al, 2002). In this report, we used intercellular dyetransfer to assess interendothelial communication in wild-type, Cx37 -/-, Cx40 -/-, Cx37 +/-Cx40 -/-and Cx37 -/-Cx40 -/-aortic segments isolated from mice of different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to connexin expression levels in EC (ie, lacking inflammatory stimuli), which have been demonstrated previously to have coregulated connexins, ie, the up or down connexin expression is dependent on the expression of other connexins. 22,28,29 How OxPAPC may decouple connexin coregulation is potentially of great interest in understanding EC response to inflammatory mediators. As the effects of OxPAPC on nuclear transcription factors become more clear (eg, Kronke et al 24 ), a more precise idea of the differential control of connexin expression will likely become more evident.…”
Section: Summary Of Changes In Connexin Expressionmentioning
confidence: 99%